2016
DOI: 10.32614/rj-2016-062
|View full text |Cite
|
Sign up to set email alerts
|

mctest: An R Package for Detection of Collinearity among Regressors

Abstract: It is common for linear regression models to be plagued with the problem of multicollinearity when two or more regressors are highly correlated. This problem results in unstable estimates of regression coefficients and causes some serious problems in validation and interpretation of the model. Different diagnostic measures are used to detect multicollinearity among regressors. Many statistical software and R packages provide few diagnostic measures for the judgment of multicollinearity. Most widely used diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
97
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(102 citation statements)
references
References 11 publications
1
97
0
4
Order By: Relevance
“…Multicollinearity among the variables in the regression models was evaluated using the variance inflation factor (VIF) and the Farrar–Glauber test (using the mctest package in R, Imdadullah, Aslam & Altaf ). Results indicated that although the predictors were moderately correlated (see Supporting Information Table S1), the VIF values for all variables ranged from 1.09 to 1.77, suggesting that multicollinearity is not an issue of concern for the regression models reported (O'brien, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multicollinearity among the variables in the regression models was evaluated using the variance inflation factor (VIF) and the Farrar–Glauber test (using the mctest package in R, Imdadullah, Aslam & Altaf ). Results indicated that although the predictors were moderately correlated (see Supporting Information Table S1), the VIF values for all variables ranged from 1.09 to 1.77, suggesting that multicollinearity is not an issue of concern for the regression models reported (O'brien, ).…”
Section: Methodsmentioning
confidence: 99%
“…Multicollinearity among the variables in the regression models was evaluated using the variance inflation factor (VIF) and the Farrar-Glauber test (using the mctest package in R, Imdadullah, Aslam & Altaf 2016).…”
Section: Multicollinearity Assessmentmentioning
confidence: 99%
“…Finally, we use the subset of subjects which had a stroke, but no rich-club involvement, to demonstrate the specificity of the rich-club nodes with respect to outcome over a simple number of region count (Ntotal) affected by the acute lesion. All analyses were performed using the computing environment R [27][28][29] .…”
Section: Model Description and Statistical Analysismentioning
confidence: 99%
“…We assayed for the potential presence of interactions among explanatory variables by generating coplots and tested for collinearity among explanatory variables (Zuur, Ieno, & Elphick, ). To do so, we visually inspected correlation matrices and calculated VIFs with the R package MCtest (Imdadullah, Aslam, & Altaf, ), with no evidence of significant collinearity among explanatory variables [all VIFs < 2 (Zuur et al, )].…”
Section: Methodsmentioning
confidence: 99%